Motivasi Berzanji terhadap Pemahaman dan Penghayatan Nilai-Nilai Islam dalam Masyarakat - Barokah, Febi Nina (Prodi Pendidikan Agama Islam IAINU Kebumen, 2024)
The implementation of the Al Barzanji activity plays an important role in society, as it has become a customary Islamic practice among the people. This activity aims to uncover the motivations behind community participation in Al Barzanji events and how these motivations can influence the understanding and appreciation of Islamic values within society. This research was conducted in the village of Purbosari, Seluma Regency. A qualitative approach was employed through in-depth interviews with members of Al Barzanji who regularly participate in monthly activities. The results indicate that the Motivation of Al Barzanji towards Understanding and Appreciation of Islamic Values in Society can be divided into two categories: 1) drawing closer to Islamic values and 2) experiencing the ritual closeness in remembering Allah. This study provides important insights into the motivations for deepening understanding and appreciation among the community.